2017
DOI: 10.1002/jbio.201600187
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of optical properties of pig esophagus by using a modified spectrometer set‐up

Abstract: Optical properties (m a , m s and g) of certain human tissue types such as skin and blood have been very well investigated. However until today, for internal body organs such as the esophagus they are not well characterized. For ex-vivo measurements "Inverse Adding Doubling" (IAD) and Inverse Monte-Carlo-Simulation (IMCS) are state of the art. Both methods need the measurement of the collimated transmission. Current methods lack a proper way of measuring the collimated transmission. Hence, this measurement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…For tissue temperature and corresponding thermal damage calculations, an esophageal tissue model with a uniform 3D grid system of 300 × 300 × 180 with a grid size of 10 μm of each dimension was used. The depth of the modeled tissue was determined by the sum of mucosa layer thickness (0.54 mm), submucosa layer thickness (0.55 mm), and muscularis layer thickness (0.63 mm) . Thermal properties of the tissue and optical properties at a wavelength of 1.5 μm have been compiled from the literature.…”
Section: Resultsmentioning
confidence: 99%
“…For tissue temperature and corresponding thermal damage calculations, an esophageal tissue model with a uniform 3D grid system of 300 × 300 × 180 with a grid size of 10 μm of each dimension was used. The depth of the modeled tissue was determined by the sum of mucosa layer thickness (0.54 mm), submucosa layer thickness (0.55 mm), and muscularis layer thickness (0.63 mm) . Thermal properties of the tissue and optical properties at a wavelength of 1.5 μm have been compiled from the literature.…”
Section: Resultsmentioning
confidence: 99%
“…The data from Holmer et al 25 is used due to the fact that Holmer et al 25 measured the optical properties from carcinoma and from healthy oesophagus. However, there is a high chance that the measurements from Holmer et al 25 have a systematic error as shown by Hohmann et al 26 . Despite the fact that they use cryo-homogenisation, this should not influence the optical properties 27 .…”
Section: Methodsmentioning
confidence: 98%
“…For the simulation, a carcinoma in oesophageal tissue is simulated due to the fact that the optical properties (μ a , μ s or g) of these tissue types is known. The optical properties are taken from the study from Holmer et al 25 instead of the own optical properties 26 . The data from Holmer et al 25 is used due to the fact that Holmer et al 25 measured the optical properties from carcinoma and from healthy oesophagus.…”
Section: Methodsmentioning
confidence: 99%
“…A uniform grid system (i.e., 100 × 100 × 100) with a mesh size of 40 × 40 × 40 µm 3 constituted the 3D structure. The thickness of the tissue sample was determined to be 4 mm, which is the sum of mucosal layer thickness (0.54 mm), submucosal layer thickness (0.55 mm), muscularis layer thickness (0.63 mm), and muscle layer (>2 mm) 9 . The third module simulated the time‐dependent heat diffusion generated by laser power density (i.e., laser irradiance) utilized as a heat source.…”
Section: Methodsmentioning
confidence: 99%